Popularity of Online Teaching English as a Foreign Language to Learners from East Asia: Teachers’ Perception - Zečević, Snežana M.; Biševac, Enes B. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Online teaching English as a foreign language to learners from East Asia has become very popular nowadays. It is a result of the intensive socio-economic development of this region’s countries, such as Japan, China, South Korea and Taiwan, which demands new roles of individuals for successful functioning in the current world. Due to following contemporary social changes, reaching the global market and adjusting the educational system to the modern concepts, English has become their obligatory school subject. The need for better language competence implies learning and improving this global language since the early age in East Asia, not only within formal education, but within the informal one as well. The lack of qualified teachers of English language and the use of inadequate teaching approaches and methods in the standard classroom resulted in the need for additional lessons, which numerous online language platforms from this region offer. For this reason, the interest in attending these lessons increased, as well as the interest in teaching English language online. The focus of this paper’s research is to introduce the main reasons for online teaching English as a foreign language to learners from East Asia and its advantages, in order to identify general causes of this job’s current popularity. It is realized through the achievement of the following aims: 1) the most frequent reasons because of which the individuals decide to teach on platforms for learning English language, which are popular among East Asian learners nowadays, are provided, and 2) the advantages of such teaching environment are examined from the teachers’ point of view. This is a cross-sectional study for the purpose of which a survey of 151 respondents worldwide was conducted by means of a self-perception questionnaire. Collected data were analysed by means of SPSS 22.0 program for statistical data analysis. The results indicate that: 1) some of the most frequent respondents’ reasons for online teaching English language to learners from East Asia are: flexible work schedule, working at home, getting a job easily, meeting new people and cultures, while 2) from the teachers’ point of view, the most common advantages of working in such environment are: feeling comfortable while teaching, flexible work schedule, satisfactory income, contact with foreign countries and cultures and less stressful environment for teaching English language.Taking into account these results, as well as the socio-economic requirements of the process of globalization in East Asia, it may be concluded that the educational concept of Hong Kong “Learning for Life, Learning Through Life” could be the policy of many Asian countries, whose aim is to enable learners to use the English language outside the classroom and learn it in a more flexible and comprehensible way. As long as the focus of teaching is not so much on form, as it is on the language functions (Pan, 2015), there will be the need for additional improvement of the English language in the countries of East Asia. Since the interest for teaching the English language within online platforms is continuing, and there are no considerable difficulties for being employed and adjusting to such work environment, it can be concluded that the future perspective of this job position is definitely guaranteed.
Keywords: English language; online teaching; East Asia; interest; popularity